Chitosan-benzofuran adduct for potential biomedical applications: Improved antibacterial and antifungal properties - Elnashar, Magdy; Abdel, L.; Awad, H.; Mouneir, S. (Scholars Research Library, 2015)
Chitosan-benzofuran adduct showed better antifungal and antibacterial properties compared to chitosan or benzofuran alone. The new polymer hydrogel has been characterized using FTIR, SEM, DSC, TGA and XRD. FTIR proved the formation of Schiff’s base reaction at 1632 cm−1, between the chitosan’s amino group and the khellinone’s ketonic group. The X-ray diffraction patterns of chitosan-benzofuran showed the formation of a porous xerogel network. The TGA and DSC results were in accordance with the results obtained from the SEM. The TGA and DSC revealed slight loss in the chitosan-benzofuran’ thermal stability compared to chitosan hydrogel and that could be regarded to the increase in porosity as shown in the SEM. The novel chitosan-benzofuran hydrogel has shown an outstanding antifungal and antibacterial effect. Moreover, the cellular cytotoxicity of baby hamster kidney cells culture by adding different concentrations of chitosan-benzofuran hydrogel were greater than those obtained from benzofuran or chitosan alone as they were 4.81±2%, 5.27±2% and 9.43±5%, respectively.